PENGARUH JOB SATISFACTION TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN ORGANIZATIONAL COMMITMENT SEBAGAI VARIABEL INTERVENING PADA RUMAH SAKIT PANTAI INDAH KAPUK DI JAKARTA - Vania, Lidya; Purba, Sylvia Diana (Jurnal Manajemen, 2014)
The purpose of this research is to test the effect of job satisfaction on Organizational Citizenship Behavior (OCB) employees Hospital Pantai Indah Kapuk (RSPIK), Jakarta mediated by organizational commitment. Data was collected using a convenience sampling. There are 70 nurses, health workers and administration used as a sample. Data analysis methods used in this research is the analysis of the path by using analytical tools of Preacher-Hayes the Simple Mediation Model. The results of data processing using SPSS 22 for windows with macros and syntax. This research findings RSPIK employees have job satisfaction, organizational commitment and OCB are relatively high, where organizational commitment can be intervening variables on job satisfaction influence on organizational citizenship behavior (OCB) at Hospital Pantai Indah Kapuk in Jakarta. Keywords: Job Satisfaction, Organizational Citizenship Behavior (OCB), and Organizational Commitment.